PENGEMBANGAN LKPD FISIKA BERBASIS PREDICT, OBERSEVE, EXPLAIN (POE) PADA MATERI FLUIDA DINAMIS KELAS XI SMA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF - Mufidhoh S, Siti; YYennita, YYennita; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The POE based worksheet minimizes the role of a teacher and gives many broadness to the trainees to make discoveries. The goal is to actively seek out knowledge according to his thinking by using sources that can be easy to solve. The main purpose of this research is to develop valid gene-based physics on dynamic materials for the 11th grade in high school. The study conducted a stage of validation by three experienced teachers of physical education. Data analysis on this study USES descriptive analysis by calculating the index of each indicator used to determine the validity of the lto which it was developed. The study provides information that the io-based physics developed on dynamic fluid-based materials are valid in high categories and can be used in learning to promote learning to be better, effective, and efficient.Keywords: LKPD, Predict Observe and Explain, Dynamic Fluid, Descriptive Analysis.